Knowledge, skills and abilities for early childhood preservice student teaches: a focus group approach - Mangwaya, Ezron (MCSER Publishing, 2016)
The purpose of this study was to establish the competences (knowledge, skills and abilities) required of effective cue)! childhood education teachers as perceived by student teachers and to suggest how competences can be acquired by student teachers before joining the teaching profession. Focus groups were conducted with student teachers who had done teaching practice and those who had not in two teachers' colleges in Masvingo province of Zimbabwe. Results indicated that specific competences were required across the domains of learning (cognitive, psychomotor and affective). Academic preparation in teachers' colleges, field experiences and exposure to role models were suggested as useful ways of acquiring competences.